IMPACT OF IMPLEMENTING CLINICAL NOTES TEMPLATES ON THE QUALITY AND CONSISTENCY OF MEDICAL DOCUMENTATION - Sultan Mohammed Ibrahim Al Askar , Majed Mohammed Alabdulaziz , Othman Nasser Fawaz Al Tamimi, Ibrahim Hamad Alsunaid, Mariam Abdullah Abdlhamid Abdulrhim, Abdullah Turki Aloraini, Tirad Rakid Mushih Alruweaili, ,; Mohammed Masoud Alfaifi, Hamdah Ali Alghamdi, Maha Sameer Alanazi, Lamyaa Ali Albulushi, Mohammed Saad Alshamre, Satam Shaya Ali, Othman Nasser Fawaz Al Tamimi, Obaid Mohammad Alsahli, (Chelonian Research Foundation, 2022)
Although there have been significant advancements in electronic health records (EHRs) in the last 25 years, there are still ongoing difficulties in implementing and using them, and the advantages achieved are not meeting expectations. The objective of this scoping assessment was to provide a comprehensive overview of the existing understanding of the impact of electronic health record (EHR) installation and the obstacles hindering the acceptance and use of EHRs. A systematic literature search was performed in the databases PubMed, Web of Science, and ACM Digital Library. Both beneficial and detrimental consequences of EHR deployment were observed, pertaining to clinical tasks, data and information management, patient care, and economic ramifications. The main challenges to acceptance and usage that were regularly seen were limited resources, inadequate training and technical assistance for users, as well as low literacy and technological abilities. While this review did not do a thorough investigation of the quality of the articles included, it did find a lack of consistency in the use of EHR terminology and the absence of specific contextual information about the research settings. Keywords: electronic health record; personal health record; scoping review; implementation; adoption